Diffusion-based reverse membrane bioreactor for simultaneous bioconversion of high-inhibitor xylose-glucose media. (September 2018) - Mahboubi, Amir; Lundin, Magnus; Doyen, Wim; De Wever, Heleen; Taherzadeh, Mohammad J.
Graphical abstract: Highlights: Reverse membrane bioreactor was used for ethanol fermentation from synthetic medium. Membrane-encased yeast cells could readily convert up to10 g/l furfural. Enhanced co-consumption of total glucose and xylose was achieved in rMBR. Simultaneous sugar and furfural conversion occurred in medium with 2.5 g/l furfural. Abstract: Two of the main hurdles in industrial production of second generation bioethanol are the high content of inhibitory compounds and presence of sequentially fermented hexose and pentose saccharides in the feedstock. In order to tackle these issues, the novel cell confinement approach in a reverse membrane bioreactor (rMBR), used in this study, proved to be promising for robust fermentation of high-inhibitory xylose-glucose media simulating a lignocellulosic hydrolysate. The high local cell concentration and concentration-driven diffusion-based mass transfer conditions in rMBR enhanced simultaneous utilization of sugars and boosted cell furfural tolerance/detoxification capacity. The diffusion rates of all compounds through the membrane were measured in a diffusion cell and in an rMBR. In the rMBR, yeast cells could readily convert high content of furfural (10 g/l) that is toxic to freely-suspended cells. Moreover, in the presence of 2.5 g/l of furfural, cells had the same performance as in medium with no inhibitor and could simultaneously convert glucose, xylose, and furfural with the latter two at the same rate with no lag phase. The performance of rMBR in remediating issues revolving around lignocellulosic bioethanol production covers the shortcomings of the conventional encapsulation technique and opens new areas of application for diffusion-based bioconversion systems.